Pengaruh Kepemimpinan Pelayanan Publik di Kecamatan Tomohon Utara Kota Tomohon - Kawet, Yehezkiel Dayan (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT: In the several year, the public serve still be a main factor, about good or not good in some serve institute. With a good serve, so the institute is the good one too. The public serve can’t avoid from the leadership in that institute. Leadership also can be an one factor of success or bad in some institute, also leadership can determined for good or bad that institute too. This research’s point is know that there is an side-effect of leadership against public serve in the Tomohon City for North Tomohon or not.This research using quantity method, there is a several statistical variable from the many indicator: the decision making, organization, giving motivation, communication, supervision. At the same time, the public serve’s indicator is : touchable, reliably, intelligent, assurance, and emphaty. The 120 employees are taking for respondents that separated in the sub-district office and 3 village office. This responden are given list question with using interview method.The result of this research has showed that leadership have a relationship with public serve in the significant extent 0,05 or confidence extent 95%. It’s can we have from the chi-square value 11,30 and critical table for significant extent 0,05 for level 4 is 10,19. In the result for coefficient contigency’s number is very to much distance from the coefficient contigency’s maximum number and just almost approach of half value from coefficient contigency’s maximum number. It can being interpretation that the level relationship between leadership and public serve is in high category.In based results of the analysis’s above, can given conclusion that leadership have a significant relationship in the high extent against public serve at North Tomohon sub-district’s institute.Keyword : Side-effect of leadership against public serve